DIGITAL PATHOLOGY AND AI: A PARADIGM SHIFT IN PATHOLOGY EDUCATION - Ritcha Saxena; Kevin Carnewale; Kapil Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
From transferring microscope images to telepathology and whole-slide imaging scanners, digital pathology's evolution spans a century. Today, digital pathology and AI are revolutionizing medical education. With digital pathology, students can access a vast repository of virtual slides, enabling them to study diseases and conditions more comprehensively. AI enhances this by aiding in image analysis, diagnosis, and pattern recognition, providing students with valuable insights and preparing them for real-world challenges in medicine. Recent advancements strongly impact its adoption, influencing medical education. Digital pathology streamlines data storage, remote communication, and AI potential. Interactive AI-driven platforms offer tailored learning experiences, fostering critical thinking and are adaptable to each student's pace and need. Integrating digital pathology and AI transforms medical education, enabling comprehensive disease study through virtual slides. This fusion adequately prepares the physicians of tomorrow, enhancing practical expertise and pathology education. The future sees AI and digital pathology integral to medical education, equipping the future physicians to navigate evolving technology and deliver exceptional care. Embracing this duo ensures readiness for the dynamic healthcare landscape